Île Dumet (Armorican Massif, France) and its glaucophane eclogites: the little sister of Île de Groix - G. Godard; D. C. Smith; D. C. Smith; D. Jaujard; S. Doukkari; S. Doukkari (European Journal of Mineralogy, 2024)
Blueschist-facies rocks are scarce within the Variscan orogen. Two main occurrences are known in the Armorican Massif (NW France), at Île de Groix and Bois-de-Céné. Another glaucophane occurrence was discovered in 1988 but went unnoticed; it is located on Île Dumet, an uninhabited island off the coast of southern Brittany, in the estuary of the river Vilaine. Orthogneiss occurs on the SW half of the island; the original granitoid magma had intruded mica schists on the NE half, where numerous 1 to 10 m long boudins of mafic rocks occur. These lenses are typically retrogressed into plagioclase-bearing amphibolite, but a few contain remnants of glaucophane-bearing eclogite, which also occurs as numerous loose blocks along the NE coast of the island, suggesting that the best-preserved eclogites lie in situ offshore in that direction.